Kontribusi Platform Digital Sosial Terhadap Peningkatan Ketertarikan Siswa pada Perguruan Tinggi Baru di Indonesia - Agung Yuliyanto Nugroho; Joko Sutopo; Nur Rohman (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Universities as institutions providing educational services must be able to adapt to this. Currently, there are many universities that use social media, but not many universities can make optimal use of social media. Promotion is something that every company must do. The main thing in promotion is to create a persuasive message that is effective to attract the attention of consumers. The use of social media for prospective new students. This study aims to decipher the influence of social media use on the number of new students. This research is a quantitative descriptive research. The sample was taken from users of 9 digital platforms Youtube, Facebook, Tik Tok, Instagram, Twitter, Sportify, ClubHouse, Pintrest and Linkedin. Based on the results of the research, the use of digital platforms to increase the number of university students is increasing. This paper seeks to outline how the trend of social media use in universities, what social media platforms can be used in universities and how social informatics is the use of digital social media platforms for universities.